Bugis Philosophy of Life in Religious Harmony: George Simmel's Perspective - Alam Khaerul Hidayat; Masita (HISTORICAL: Journal of History and Social Sciences, 2024)
This paper examines efforts to realize religious harmony in society by applying the Bugis philosophical concepts of "Sipakatau, Sipakainge, Sipakalebbi." The purpose of this research is to describe and analyze the meaning or philosophy contained in the Bugis philosophy and to propose implementations that can be applied in social life to achieve integration and religious harmony. In this regard, the author employs qualitative research by reviewing books and published research results and exploring relevant literature sources related to this research, specifically the tradition of "Sipakatau, Sipakainge, Sipakalebbi" as a manifestation of religious harmony in society, which will be analyzed and then reflected upon using a philosophical approach. From this effort, the researcher finds that the concept of "Sipakatau, Sipakainge, Sipakalebbi" is highly relevant to George Simmel's theory, which emphasizes the ways of interacting with society. The theories of sociability, superordination, and conflict provide a concept of society through reciprocal interactions. Society is viewed as more than just a collection of individuals; it refers to patterns of reciprocal interactions between individuals. This principle is continuously practiced by the community to achieve religious harmony in Indonesia, especially amidst the strong currents of globalization.